High critical current density over 1 MA cm−2 at 13 T in BaZrO3 incorporated Ba(Fe, Co)2As2 thin film. (5th July 2017) - Lee, Jongmin; Jiang, Jianyi; Kametani, Fumitake; Oh, Myeong Jun; Weiss, Jeremy D; Collantes, Yesusa; Seo, Sehun; Yoon, Sejun; Tarantini, Chiara; Jo, Youn Jung; Hellstrom, Eric E; Lee, Sanghan
Abstract: Achieving high critical current density ( J c ) under a high magnetic field in Fe based superconductors is indispensable for practical applications. Here we report that high critical current density over 1 MA cm −2 in high field (13 T) can be achieved in BaZrO3 (BZO) incorporated Ba(Fe, Co)2 As2 (Co-Ba122) thin film grown on CaF2 substrate using pulsed laser deposition. The magnetization J c of Co-Ba122 thin film incorporated with 2 mol.% BZO reaches 1.3 MA cm −2 ( H ǁ c, 13 T and 4.2 K), 14 times higher than that of pure Co-Ba122 thin film. Transmission electron microscopy observation revealed that BZO forms nanorods of ∼4 nm in average diameter with mean separation of 10–11 nm which corresponds to a matching field of about 17–20 T. Incorporating BZO in Co-Ba122 thin films led to a strong vortex pinning effect and a significant enhancement of J c because a high density of BZO nanorods could form in the superconducting matrix without significant degradation of T c, and the diameter of BZO nanorods is approximately twice the coherence length of Co-Ba122 ( ξ ab (0) ∼ 2.5 nm) which is the optimal size as pinning centers.